Intrinsically microporous polyimides containing spirobisindane and phenazine units: Synthesis, characterization and gas permeation properties. Issue 7 (4th January 2018) - Shrimant, Bharat; Dangat, Yuvraj; Kharul, Ulhas K.; Wadgaonkar, Prakash P.
ABSTRACT: A new diamine containing spirobisindane and phenazine units, namely, 3, 3, 3′, 3′‐tetramethyl‐2, 2′, 3, 3′‐tetrahydro‐1, 1′‐spirobi[cyclopenta[b]phenazine]‐7, 7′‐diamine (TTSBIDA) was synthesized starting from commercially available 5, 5′, 6, 6′‐tetrahydroxy‐3, 3, 3′, 3′‐tetramethyl‐1, 1′‐spirobisindane (TTSBI). TTSBI was oxidized to 3, 3, 3′, 3′‐tetramethyl‐2, 2′, 3, 3′‐tetrahydro‐1, 1′‐spirobi[indene]‐5, 5′, 6, 6′‐tetraone (TTSBIQ) which was subsequently condensed with 4‐nitro‐1, 2‐phenylenediamine to obtain 3, 3, 3′, 3′‐tetramethyl‐7, 7′‐dinitro‐2, 2′, 3, 3′‐tetrahydro‐1, 1′‐spirobi[cyclopenta[b]phenazine] (TTSBIDN). TTSBIDN was converted into TTSBIDA by reduction of the nitro groups using hydrazine hydrate in the presence of Pd/C as the catalyst. A series of new polyimides of intrinsic microporosity (PIM‐PIs) were synthesized by polycondensation of TTSBIDA with commercially available aromatic dianhydrides. PIM‐PIs exhibited amorphous nature, high thermal stability ( T 10  > 480 °C) and intrinsic microporosity (BET surface area = 59–289 m 2 /g). The gas permeation characteristics of films of selected PIM‐PIs were evaluated and they exhibited appreciable gas permeability as well as high selectivity. The CO2 and O2 permeability of PIM‐PIs were in the range 185.4–39.2 and 30.6–6.2 Barrer, respectively. Notably, polyimide derived from TTSBIDA and 4, 4′‐(hexafluoroisopropylidene)diphthalic anhydride (PIM‐PI‐6FDA) exhibited high CO2 and O2 permeability of 185.4 and 30.6 Barrer with CO2 /CH4 and O2 /N2 selectivity of 43.1 and 5.1, respectively. The data of PIM‐PI‐6FDA for CO2 /CH4 and O2 /N2 gas pairs were located near Robeson upper bound. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 766–775 Abstract : A new series of intrinsically microporous polyimides (PIM‐PIs) containing spirobisindane and phenazine units were synthesized by polycondensation of 3, 3, 3′, 3′‐tetramethyl‐2, 2′, 3, 3′‐tetrahydro‐1, 1′‐spirobi[cyclopenta[b]phenazine]‐7, 7′‐diamine (TTSBIDA) with aromatic dianhydrides. The gas permeability studies of PIM‐PIs demonstrated appreciable permeability and high selectivity.